2016
DOI: 10.1371/journal.pone.0154560
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream-To-Eye Infections Are Facilitated by Outer Blood-Retinal Barrier Dysfunction

Abstract: The blood-retinal barrier (BRB) functions to maintain the immune privilege of the eye, which is necessary for normal vision. The outer BRB is formed by tightly-associated retinal pigment epithelial (RPE) cells which limit transport within the retinal environment, maintaining retinal function and viability. Retinal microvascular complications and RPE dysfunction resulting from diabetes and diabetic retinopathy cause permeability changes in the BRB that compromise barrier function. Diabetes is the major predispo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Choroidal neovascularization has been observed in a sub-population of patients diagnosed with GA and points to disruption of the outer blood-retinal barrier 6 , 7 . To address the in vivo consequences of complement activation on POS, we recapitulated RPE cell death and loss of outer blood-retina barrier (BRB) function by treating mice with NaIO 3 39 that induces death of RPE within hours 40 , 41 . This is accompanied by transient edema as measured by spectral domain-optical coherence imaging (SD-OCT) 42 and fluorescein dye and albumin leakage 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Choroidal neovascularization has been observed in a sub-population of patients diagnosed with GA and points to disruption of the outer blood-retinal barrier 6 , 7 . To address the in vivo consequences of complement activation on POS, we recapitulated RPE cell death and loss of outer blood-retina barrier (BRB) function by treating mice with NaIO 3 39 that induces death of RPE within hours 40 , 41 . This is accompanied by transient edema as measured by spectral domain-optical coherence imaging (SD-OCT) 42 and fluorescein dye and albumin leakage 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies from our laboratory and others have shown that BRB dysfunction allows the entry of infectious agents into the retina/vitreous cavity and causes inflammation and tissue damage (48,49). A recent study by Miner, Apte, and colleagues provided the first evidence of ZIKV RNA in the eyes of subcutaneously challenged IFNRA1 -/-mice (27), but the cellular mechanisms by which ZIKV invaded the eye were not elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic mice are prone to developing endogenous endophthalmitis; that is, bacteria injected intravenously can penetrate the barrier between the blood vessels and the vitreous humor. Mice not rendered diabetic demonstrated the movement of bacteria from the blood to vitreous in only 7% of the cases whereas mice rendered diabetic for 3 months experienced bacterial movement from the blood to the vitreous in 58% of the animals [ 179 , 180 ].…”
Section: Endophthalmitismentioning
confidence: 99%